TBK1 at the Crossroads of Inflammation and Energy Homeostasis in Adipose Tissue - Zhao, Peng; Wong, Kai in; Sun, Xiaoli; Reilly, Shannon M.; Uhm, Maeran; Liao, Zhongji; Skorobogatko, Yuliya; Saltiel, Alan R. (Cell, 2018)
The noncanonical IKK family member TANK-binding kinase 1 (TBK1) is activated by pro-inflammatory cytokines, but its role in controlling metabolism remains unclear. Here, we report that the kinase uniquely controls energy metabolism. Tbk1 expression is increased in adipocytes of HFD-fed mice. Adipocyte-specific TBK1 knockout (ATKO) attenuates HFD-induced obesity by increasing energy expenditure; further studies show that TBK1 directly inhibits AMPK to repress respiration and increase energy storage. Conversely, activation of AMPK under catabolic conditions can increase TBK1 activity through phosphorylation, mediated by AMPK’s downstream target ULK1. Surprisingly, ATKO also exaggerates adipose tissue inflammation and insulin resistance. TBK1 suppresses inflammation by phosphorylating and inducing the degradation of the IKK kinase NIK, thus attenuating NF-κB activity. Moreover, TBK1 mediates the negative impact of AMPK activity on NF-κB activation. These data implicate a unique role for TBK1 in mediating bidirectional crosstalk between energy sensing and inflammatory signaling pathways in both over- and undernutrition. [Display omitted] •TBK1 operates at the intersection of energy expenditure and inflammation•TBK1 deficiency attenuates HFD-induced obesity but exaggerates inflammation•TBK1 represses energy expenditure by phosphorylating and inhibiting AMPK•TBK1 attenuates NF-κB activation and mediates the anti-inflammatory effect of AMPK Adipose tissue inflammation plays an important role in reducing energy expenditure in obesity.